2019
DOI: 10.4103/ija.ija_69_19
|View full text |Cite
|
Sign up to set email alerts
|

Hemi-diaphragmatic paresis following extrafascial versus conventional intrafascial approach for interscalene brachial plexus block: A double-blind randomised, controlled trial

Abstract: Background and Aims: Hemidiaphragmatic paresis occurs in almost all patients undergoing interscalene block for proximal upper limb surgeries. This study tested hypothesis that ultrasound-guided extrafascial approach of interscalene block under nerve stimulator guidance reduces incidence of hemidiaphragmatic paresis in comparison to intrafascial approach by achieving same degree of anaesthesia and analgesia. Methods: Sixty patients undergoing proximal upper limb surgerie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(33 reference statements)
0
8
1
Order By: Relevance
“…The different dose can explain the difference between the two studies. Ayyanagouda and his colleagues [15] disagreed with our findings as they proved that post-procedural FVC, FEV 1 and PEF in the extrafascial injection group was significantly higher compared to intrafascial injection group. This difference may be due to the different type and volumes of anesthesia used (ropivacaine versus bupivacaine).…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…The different dose can explain the difference between the two studies. Ayyanagouda and his colleagues [15] disagreed with our findings as they proved that post-procedural FVC, FEV 1 and PEF in the extrafascial injection group was significantly higher compared to intrafascial injection group. This difference may be due to the different type and volumes of anesthesia used (ropivacaine versus bupivacaine).…”
Section: Discussioncontrasting
confidence: 93%
“…These results are supported by findings of Palhais et al [9] Furthermore, Sowmiya et al ([12] proved that onset of motor and sensory blockage were substantially delayed in ~ 8 ~ extrafascial injection than intrafascial injection. In another study, [15] the onset of motor and sensory blockage was faster after intrafascial contrasted to extrafascial ISBPB. The current study showed that the time to first analgesic request and numerical rating scale (NRS) were similar for both groups in the 1 st 24 hours.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…2.274 L LVISB vs ISO block P < 0.001 73 1 HDP in the PACU; 32 vs 2 23 0.315 Bao et al, [ 26 ] 2019 Reg Anesth Pain Med. 5.564 L 20 mL vs 30 mL SCB P = 0.03 74 6 HDP at 30 min after block; 14 vs 23 0 0 Ayyanagouda et al, [ 40 ] 2019 Indian J Anaesth. / L IF- vs EF-ISB P < 0.001 60 1 HDP at 30 min after block; 14 vs 5 1 0.017 Kang et al, [ 41 ] 2018 Reg Anesth Pain Med.…”
Section: Resultsmentioning
confidence: 99%
“…These techniques have reduced the chance of paresis to as low as 20% (7). Ultrasound-guided ISB with the aid of nerve stimulator through extrafascial approach reduces the risk of diaphragmatic paresis and pulmonary impairment when compared with intrafascial approach (8).…”
Section: Discussionmentioning
confidence: 99%